Modeling of the thermopiezoelastic behavior of prismatic smart composite structures made of orthotropic materials - Challagulla, Krishna S.; Kalamkarov, Alexander L.; Georgiades, Tasos (My University, 2006)
Asymptotic homogenization models for prismatic smart composite structures are derived and the effective elastic, piezoelectric, and thermal expansion coefficients are obtained. The actuation coefficients characterize the intrinsic transducer nature of active smart materials that can be used to induce strains and stresses in a coordinated fashion. Examples of such actuators employed with smart composite material systems are derived from piezoelectric, magnetostrictive and some other materials. The constituents of the smart structures are assumed to exhibit orthotropic characteristics. The original problem for the regularly non-homogeneous smart composite structure reduces to a system of three simpler types of problem, called unit cell problems. It is precisely these unit cell problems that enable the determination of the aforementioned coefficients. These effective coefficients are universal in nature and can be used to study a wide variety of boundary value problems associated with a smart structure of a given geometry.
Keywords: Boundary value problems; Magnetostrictive transducers; Expansion (Heat)